2018
DOI: 10.1097/md.0000000000009676
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinally extensive transverse myelitis with pulmonary tuberculosis

Abstract: Rationale:Longitudinally extensive transverse myelitis (LETM) is characterized by contiguous inflammatory lesions of spinal cord extending to ≥3 vertebral segments. The etiology of LETM is complicated, including various infection, autoimmune disease, and so on. Neuromyelitis optic spectrum disorder (NMOSD) is the most common cause of LETM. Several case reports have suggested the associations between NMOSD and pulmonary tuberculosis (PTB).Patient concerns:Patient 1, a 20-year-old woman who had a past history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…[ 6 7 ] Clinico-radiological differential diagnoses are summarized [see Table 1 ]. [ 5 7 10 11 12 13 14 15 16 17 18 19 20 ] Tubercular LETM is postulated to be a result of an abnormal activation of immune response against cord. [ 21 ] Immune-mediated inflammatory secondary demyelination has been the explanation for NMOSD cases associated with pulmonary TB[ 14 ] but causative association is doubtful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 7 ] Clinico-radiological differential diagnoses are summarized [see Table 1 ]. [ 5 7 10 11 12 13 14 15 16 17 18 19 20 ] Tubercular LETM is postulated to be a result of an abnormal activation of immune response against cord. [ 21 ] Immune-mediated inflammatory secondary demyelination has been the explanation for NMOSD cases associated with pulmonary TB[ 14 ] but causative association is doubtful.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Exact pathogenesis of LETM in TB is yet to be elucidated, however, an immune-inflammatory response to the infectious agent or the infection itself has been postulated as a cause in previous literatures. [ 7 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have considered a combination of steroid and antitubercular therapy to be appropriate. 3 4 18 41 42 43 44 Antiretroviral therapy may be added to the treatment regime for patients with HIV. All of the reported patients analyzed in this review received a combination of steroid and antitubercular therapy, with follow-up clinical and radiological improvements evident in most of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported similar phenomenon in a young female. 8 Wisniewski Bloom reported demyelination and inflammatory response after injecting BCG into sensitized guinea pigs. 9 Mycobacterium tuberculosis may have common antigens with myelin basic protein.…”
Section: Discussionmentioning
confidence: 99%